Building consensus for social and economic reconstruction (IDB WashingtonUS, 1994)
Presents a policy agenda which examines aspects such as policy issues for socioeconomic reform; the human condition; macro-economic and financial considerations; infrastructure, housing and public utilities; the productive and social sectors; poverty and strategic interventions; and finally, community governance, administrative decentralization and public participation in the development process. Looks at sectoral issues and makes recommendations.
DC